Teknik sederhana pembuatan gigitiruan jembatan tiga unit dari komposit A simple technique to make three-unit composite bridge - Edy Machmud (Journal of Dentomaxillofacial Science, 2011)
Denture treatment has the objective to enhance mastication and aesthetics function of patients. Recently, fixedpartial dentures, crowns or bridges are popular restoration in population. The materials usually used for therestoration are acrylic, porcelain, composite, and metal. Composite is used due to patient’s unability to comeseveral times. This case report will discuss the technique of making three unit bridge using composite materials.This composite restoration is used because the colors can be matched with natural tooth colors and completed inone visit